Evaluation of Genetic Merit of Buffaloes by Direct Sequencing - Gangaraj, Darshan Raj (Journal of Buffalo Science, 2012)
Sequencing the genome of the buffaloes enables scientists to more accurately identify the genetic markers that are responsible for economically important traits such as milk yield, milk fat and protein. Producers can use that information to breed healthier dairy animals that produce more and higher quality milk as well as beef animals. Consumers will benefit from more cost-effective and healthier products on store shelves. Understanding what genes contribute to specific buffalo animal traits will also have spinoff applications related to other fields like human health and disease. The animals used in the genome project have had a high impact on the breeding and commercial sectors in dairy and beef.